Moving from long case to scenario-based clinical examination: Proposals for making it feasible. - Thomas, Puthiaparampil T.; Md Mizanur, Rahman; Shazrina, Ahmad Razali; Sabrina, Lukas; Nariman, Singmamae; Chee Shee, Chai; Abg Safuan, Adenan (Medical Association Malaysia, 2022)
Introduction: Our faculty used one long case (LC) and three short cases for the clinical component of the final professional examinations. During the COVID-19 pandemic, the LC had to be replaced with scenario-based clinical examination (SBCE) due to the impracticability of using recently hospitalised patients. While keeping the short case component as usual, the LC had to be replaced with SBCE in 2020 for the first time at a short notice. To evaluate the positive and negative aspects of SBCE and LC to determine the feasibility of replacing LC with SBCE in future examinations. Materials and methods: We compared the LC scores of three previous years with those of the SBCE and studied the feedback of the three stakeholders: students, examiners, and simulated patients (SPs), regarding their experience with SBCE and the suitability of SBCE as an alternative for LC in future examinations. Results: The SBCE scores were higher than those of the LC. Most of the examiners and students were not in favour of SBCE replacing LC, as such. The SPs were more positive about the proposition. The comments of the three stakeholders brought out the plus and minus points of LC and SBCE, which prompted our proposals to make SBCE more practical for future examinations. Conclusion: Having analysed the feedback of the stakeholders, and the positive and negative aspects of LC and SBCE, it was evident that SBCE needed improvements. We have proposed eight modifications to SBCE to make it a viable alternative for LC.